0
Ausgangsfunktion:
\( \frac {2x²+5} {x-1} \)
Ableitung 1:
\( \frac {2x²-4x-5} {(x-1)²} \)
Mitternachtsformel Ergebnisse:
x1 = \(\frac {4+ \sqrt{56}} {4} \)
x2 = \(\frac {4- \sqrt{56}} {4} \)
Wie komme ich auf die Endlösung
x1/2 = \(\frac {2+- \sqrt{14}} {2} \)?
\( \frac {2x²+5} {x-1} \)
Ableitung 1:
\( \frac {2x²-4x-5} {(x-1)²} \)
Mitternachtsformel Ergebnisse:
x1 = \(\frac {4+ \sqrt{56}} {4} \)
x2 = \(\frac {4- \sqrt{56}} {4} \)
Wie komme ich auf die Endlösung
x1/2 = \(\frac {2+- \sqrt{14}} {2} \)?
Diese Frage melden
gefragt
dietergletz
Punkte: 46
Punkte: 46